Path Model: Effect of Knowledge, Personality and Behavior Intentions toward Climate Change Adaptive Behavior - Tarmana, Dede; ., Nadiroh; Purwanto, Agung (International Journal of Membrane Science and Technology, 2023)
This study was aimed at modelling of climate change adaptive behaviour from basic model theory Responsible Environmental Behaviour (REB) by Hines, and to know the effect of knowledge about climate change (CC), personality, behavior intention toward CC adaptive behavior. A survey method was used by involving 481 Cadets at The School of Meteorology Climatology and Geophysics (STMKG) as sample in this study. There were 4 instruments in this research for measuring knowledge about CC (24 items, reliability .923), personality (25 items, reliability .933), behavior intention (34 items, reliability .976) and CC adaptive behavior of cadets (24 items, reliability .964). Data was analyzed by descriptive statistical, path modelling analysis and inferential statistics. The results revealed that path model at CC adaptive behavior have the significant suitability model. CC adaptive behavior significantly direct and indirect affected knowledge about CC, personality, and behaviour intention, but unaffected indirectly by knowledge about CC. Based on those findings, it can be concluded that variations in CC adaptive behavior of STMKG cadets are affected by variations in knowledge about CC, personality, and behaviour intention. It means that Path model can used to predict CC adaptive behavior based on knowledge about CC, personality, and behavior intention.